Survival of adult AIDS patients in a reference hospital of a metropolitan area in Brazil - Guerreiro Maria F; Kerr-Pontes Ligia RS; Mota Rosa S; França Jr. Marcondes C; Távora Fábio F; Caminha Iusta (Universidade de São Paulo, 2002)
OBJECTIVE: To evaluate the influence of sociodemographic, clinical, and epidemiological factors in AIDS patients survival in a reference hospital. METHODS: A sample of 502 adult AIDS patients out of 1,494 AIDS cases registered in a hospital in Fortaleza, Brazil, was investigated between 1986 and 1998. Sixteen cases were excluded due to death at the moment of the AIDS diagnosis and 486 were analyzed in the study. Socioeconomic and clinical epidemiological were the variables studied. Statistical analysis was conducted using the Kaplan-Meier survival analysis and the Cox proportional hazards model. RESULTS: Three hundred and sixty two out of the 486 patients studied took at least one antiretroviral drug and their survival was ten times longer than those who did not take any drug (746 and 79 days, respectively, p <0.001). Patients who took two nucleoside reverse transcriptase inhibitors (NRTI) plus protease inhibitor were found to have higher survival rates (p <0.001). The risk of dying in the first year was significantly lower for patients who took NRTI and a protease inhibitor compared to those who took only NRTI. In addition, this risk was much lower from the second year on (0.10; 95%CI: 0.42-0.23). The risk of dying in the first year was significantly higher for less educated patients (15.58; 95%CI: 6.64-36.58) and those who had two or more systemic diseases (3.03; 95%CI: 1.74-5.25). After the first year post-diagnosis, there was no risk difference for these factors. CONCLUSIONS: Higher education revealed to exert a significant influence in the first-year survival. Antiretroviral drugs had a greater impact in the survival from the second year on. A more aggressive antiretroviral therapy started earlier could benefit those patients.